2018
DOI: 10.21273/hortsci12714-17
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Flowering Responses of Four Bedding Plant Species to a Range of Red to Far Red Ratios

Abstract: In greenhouse ornamental crop production, bedding plants grown below high densities of hanging baskets (HBs) tend to be of lower quality. Hanging basket crops can decrease the red to far red ratio (R:FR) of the growing environment below; however, the extent to which decreased R:FR affects plant morphology and flowering of the lower-level crops is unknown. The present study examined effects of R:FR on morphology and flowering of marigold ‘Antigua Orange’ (Tagetes erecta), petu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…High LI-mediated reductions in HL may have important ramifications for microgreen production as shorter HL may increase overall crop robustness and lengthen postharvest shelf life; however, shorter HL can also increase difficulty of harvesting, particularly if harvesting is done by machine. Depending on the importance of HL at harvest, relative to other production metrics (e.g., yield), it may be possible to counteract the LI-induced reductions in HL by using targeted light spectrum treatments such as a reduced photon flux ratio of R to FR light (Blom et al, 1995;Fletcher et al, 2005;Hisamatsu et al, 2008;Mah et al, 2018) or monochromatic blue light treatments (Hata et al, 2013;Hern andez and Kubota, 2016;Kim et al, 2014;Kong et al, 2018) to stretch the plants. Probably the most important harvest metric for commercial microgreen production is fresh yield (i.e., kg (FW)• m -2 ) because microgreens are typically sold on a ''per-FW'' basis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High LI-mediated reductions in HL may have important ramifications for microgreen production as shorter HL may increase overall crop robustness and lengthen postharvest shelf life; however, shorter HL can also increase difficulty of harvesting, particularly if harvesting is done by machine. Depending on the importance of HL at harvest, relative to other production metrics (e.g., yield), it may be possible to counteract the LI-induced reductions in HL by using targeted light spectrum treatments such as a reduced photon flux ratio of R to FR light (Blom et al, 1995;Fletcher et al, 2005;Hisamatsu et al, 2008;Mah et al, 2018) or monochromatic blue light treatments (Hata et al, 2013;Hern andez and Kubota, 2016;Kim et al, 2014;Kong et al, 2018) to stretch the plants. Probably the most important harvest metric for commercial microgreen production is fresh yield (i.e., kg (FW)• m -2 ) because microgreens are typically sold on a ''per-FW'' basis.…”
Section: Discussionmentioning
confidence: 99%
“…Gerovac et al (2016) speculated that the presence of far-red (FR, 700 to 800 nm) in one of their PFR treatments could have induced shade avoidance responses characteristic of growing environments with low photon flux ratios of red (R, 600 to 700 nm) to FR (R:FR) in some of the genotype • LI treatment combinations. However, shade avoidance responses are normally observed when plants are exposed to R:FR that are substantially lower than parity (Blom et al, 1995;Fletcher et al, 2005;Mah et al, 2018). Therefore, a shade avoidance response was highly unlikely in this growing environment, particularly because the shoot apical meristem of individual plants would not have been subject to substantial amounts of vegetated shade.…”
mentioning
confidence: 98%
“…Stem elongation is a typical shadeavoidance response mediated by phytochrome, which detect changes in the R:FR ratio (Franklin, 2008;Morgan and Smith, 1981;Ruberti et al, 2012). Creating a far-red deficient light environment can reduce stem elongation of ornnamental plants (Runkle and Heins, 2002), while adding far-red light can increase stem elongation (Li and Kubota, 2009;Mah et al, 2018;Park and Runkle, 2017;Yang et al, 2012). As far-red light increased from 4.0 to 68.8 mmolÁm -2 Ás -1 in this study, plant height increased linearly from 8.4 to 11.6 cm, or by 38% (Fig.…”
Section: Morphological Responsementioning
confidence: 99%
“…Although few studies directly investigate whether the changes in light quality during twilight actually influence stem elongation, Lund et al (2007) found that height of chrysanthemum (Chrysanthemum •morifolium) increased as R:FR was reduced from 2.4 to 0.7 or 0.4 to mimic twilight (using LEDs), under very low photosynthetic photon flux density [PPFD (400-700 nm)] by maintaining either R at 1 mmolÁm -2 Ás -1 or FR at 1 mmolÁm -2 Ás -1 for 30 min at the end of photoperiod in growth chambers. A previous growth chamber study showed that four bedding plant species grown under a light spectrum with R:FR of 0.7 vs. 1.1 had longer stems (Mah et al, 2018), although it is uncertain whether this result would still be observed if R:FR was altered during twilight only.…”
mentioning
confidence: 99%
“…Light-emitting diodes (LEDs) are a promising tool for manipulating plant morphology due to the customizable nature of LED spectra, as targeted light spectral modifications can have substantial photomorphological effects. For example, the red [R (600-700 nm)] to far red [FR (700-800 nm)] photon flux ratio (R:FR) can dramatically affect plant morphology in solesource lighting scenarios (Carvalho and Folta, 2014;Demotes-Mainard et al, 2016;Hern andez et al, 2016;Holmes and Smith, 1977a;Kong et al, 2018;Mah et al, 2018). The challenge remains to design suitable and cost-effective growth control treatments using LEDs in greenhouse production environments, where targeted supplemental light treatments must overcome the background intensity and quality characteristics of natural light to elicit photomorphogenic effects.…”
mentioning
confidence: 99%